Supply chain management: a review from the logistics and environment (2018)
This article presents a review of the research about the advance related to the Supply Chain Management and the Green Supply Chain Management. The review is done through content analysis, based on Articles published from 2005 until 2015. The investigations were classifi ed according to the subject and the focus given to each of them. During the review it was evident that the research conducted on the subject SCM is done in order to create new strategies for collaboration between the various links in the SC and investigations concerning the GSCM point to design support tools including new processes and channels within the SC, aimed to remanufacturing, reprocessing and reuse of waste or life products generated in the normal SCM.